A study of balance and gait following stroke : implications for rehabilitation - Turnbull, George Innes (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1994)
This study examined: the features and extent of the gait velocity decrement following stroke; the nature of the balance disorder and; investigated relationships between gait and balance. Twenty, fully-ambulant, hemiplegic subjects (12 men and 8 women), with a mean age of 57.2 years (± 10.7), were compared with 20 age- and sex-matched controls. Spatiotemporal gait kinematics were measured at five walking speeds ranging from "very slow" to "very fast". Balance was then measured while subjects maintained a variety of weight shift postures both with feet parallel and then in diagonal positions similar to those assumed during the double support phases of gait. Location and variability of centre of pressure (CP) were measured and the ranges over which CP could be shifted were calculated. Stroke subjects walked very slowly with their "fastest" walking speed (0.5 stat/s ± 0.23) no different from the "slowest" speed (0.38 stat/s ± 0.11) of the controls (p > 0.05). Differences between the other parameters were also found, many of which could be attributed to the differences in walking speeds. However, where the subjects walked at similar velocities, the hemiplegic sample walked with quicker and shoner strides suggesting a "cautious" gait pattern. The single support asymmetry of the strokes decreased with increasing walking speed. The positions of CP in the hemiplegic sample were found to be significantly displaced towards the unaffected leg and deficiencies were found in posterior shifts (p < 0.05). Postural sway was significantly greater in the hemiplegic sample implying less stable balance and the ranges over which the hemiplegic sample shifted weight were significantly less than the controls. The diagonal weight shift tests revealed the difficulty the stroke subjects experienced in shifting CP posterolaterally over the affected leg. Significant correlations were detected confmning the presence of relationships between static balance performance and gait. However, these correlation findings left considerable percentages of variance unexplained. These findings suggest that future rehabilitation should address the poverty of range of walking speed possessed by hemiplegic subjects as well as the reduced ability to weight shift over the hemiplegic limb, particularly posterolaterally. Further study to test these proposals is indicated.
Keywords: Cerebrovascular disease -- Physical therapy; Gait disorders; Equilibrium (Physiology); People with disabilities -- Rehabilitation